2005
DOI: 10.1577/ft03-178.1
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Tolerance of Red‐Rim Melania Melanoides tuberculatus, an Exotic Aquatic Snail Established in the United States

Abstract: The red-rim melania Melanoides tuberculatus (family Thiaridae), a tropical, nonindigenous aquatic snail, has become established and is spreading in the United States. Concerns associated with the spread of this snail include its potential to displace native snail populations and to transmit trematodes. Of particular concern is the gill trematode Centrocestus formosanus now found in U.S. commercial and wild fish stocks. The snail survives year-round in subtropical ponds and constant-temperature spring runs in F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 9 publications
1
20
0
1
Order By: Relevance
“…For M. tuberculatus, however, our findings are very similar to that of Mitchell and Brandt (2005) who reported that all M. tuberculatus exposed to 5°C died within 1 day. In addition, exposure to 35°C killed 95% of snails within 27 days, while exposure to 40°C caused complete mortality within 10 h. Our high temperature (37°C) was a midpoint between these two values and our results represent a midpoint in terms of survival (e.g.…”
Section: Discussionsupporting
confidence: 90%
“…For M. tuberculatus, however, our findings are very similar to that of Mitchell and Brandt (2005) who reported that all M. tuberculatus exposed to 5°C died within 1 day. In addition, exposure to 35°C killed 95% of snails within 27 days, while exposure to 40°C caused complete mortality within 10 h. Our high temperature (37°C) was a midpoint between these two values and our results represent a midpoint in terms of survival (e.g.…”
Section: Discussionsupporting
confidence: 90%
“…The snail can survive under hard environmental conditions, e.g. high salinity levels up to 25% (Smith 1989, Bolaji et al 2011, but is more vulnerable to low temperatures (Mitchell and Brandt 2005b, Kazibwe et al 2006, Karatayev et al 2009, Fleming et al 2011. Nonetheless, it may survive during cold winter months in artificially heated ponds, and rising water temperatures due to the climate changes may improve survival of the snail in temperate regions.…”
Section: Discussionmentioning
confidence: 99%
“…Several features allow this invasive species to dominate, including the capability of aestivating (Abílio et al 2007), tolerance to low dissolved-oxygen concentrations, high temperatures (Mitchell & Brandt 2005), and brackish and saline waters, and also because it can reproduce parthenogenetically (see references in Santos et al 2012). The dominance of M. tuberculata in rivers and reservoirs of semiarid regions in northeastern Brazil has been mentioned in the literature (e.g., Abílio et al 2006, Santana et al 2009, Lima et al 2013.…”
Section: Discussionmentioning
confidence: 99%